2005
DOI: 10.1136/gut.2004.055939
|View full text |Cite
|
Sign up to set email alerts
|

The C/C-13910 genotype of adult-type hypolactasia is associated with an increased risk of colorectal cancer in the Finnish population

Abstract: Background and aims: The role of nutrition in the pathogenesis of colorectal cancer is not fully understood. Milk products are an essential part of human nutrition in Western countries. Absorption of lactose, the main sugar of milk, is regulated by the activity of the lactase enzyme in the gut wall. The activity of lactase is genetically determined and is associated with a C/T single nucleotide polymorphism residing 13910 bp upstream of the lactase coding sequence. Here we have studied the relationship between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 33 publications
1
21
0
1
Order By: Relevance
“…47 In the Finnish population, low lactase enzyme activity, defined by genotyping of the C ⁄ T (13910) variant (LI) may increase the risk of colorectal cancer. 48 The drugs used in treatment of IBD like 5-ASA preparations and Budesonide are formulated to deliver the active ingredients topically to the distal small bowel and colon after oral ingestion. This is achieved by a pH-dependent release mechanism or through bacterial degradation.…”
Section: Discussionmentioning
confidence: 99%
“…47 In the Finnish population, low lactase enzyme activity, defined by genotyping of the C ⁄ T (13910) variant (LI) may increase the risk of colorectal cancer. 48 The drugs used in treatment of IBD like 5-ASA preparations and Budesonide are formulated to deliver the active ingredients topically to the distal small bowel and colon after oral ingestion. This is achieved by a pH-dependent release mechanism or through bacterial degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Association between this C/T -13910 variant and prostate cancer has not been studied before. However, studies about the association between this variant and other cancers have been done (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…18 -20 Until recently, no large-scale studies with genotype data have been reported from Britain, but two small studies reported prevalences of 5.4 and 9.0% of nonpersistence (C) allele homozygosity. 21,22 The latter study recruited participants from the south of England, where the prevalence of non-persistence (C) allele homozygosity in our study was higher than in the north of Britain. There was no evidence of an age difference by genotype, and there was no strong evidence of departure from the Hardy-Weinberg equilibrium either at younger or older ages, suggesting that in this population genotype is not related to survival.…”
Section: Discussionmentioning
confidence: 99%